Comparison of Efficacy of Pregabalin Vs Duloxetine in Peripheral Neuropathy Pain in Type 2 Diabetic Patients at Low Doses - Sumayya Shabbir, Asif Islam, Amer Zohaib, Tooba Fatima, Saima Riaz, Uzma Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This research is specifically designed to compare the efficacy, safety and dosage pattern of DLX and PGB in peripheral neuropathy pain in type 2 diabetic patients . In this clinical trial, we have used a low dosage of both drugs to measure the outcomes. Place and Duration: Mayo Hospital Endocrine Out Patient Department . 01-01-2022 to 31-03-2022 Study type: Randomized controlled clinical trial Methodology: All the patients were randomly divided into two equal groups of pregabalin and duloxetine. For this study, some empty capsules were prepared which were filled with either duloxetine, pregabalin, or starch as a placebo. Initially, patients of the duloxetine group received a placebo capsule once daily as a washout period for ten days. Later on, they received a fixed dose of 30 mg/d duloxetine in the first week of treatment and different doses of 30 mg/d to 60 mg/d were used for the next eleven weeks based on drug efficacy and tolerability. However, the group of pregabalin patients received a placebo capsule twice a day for ten days as a washout period. After that, they received 75 mg/Bd for the first week of treatment and 75 mg/Bd to 150 mg/Bd for eleven weeks of treatment. Results: The current study reported 74% ADRs in the duloxetine group while pregabalin reported 37% adverse reactions to medication. The significant mean difference related to incidents was observed as (p<0.05, =0.01 and <0.001) between both groups. In some cases, mild and tolerable adverse reactions were reported however severe reactions led to discontinuation of the drug. In 19% of cases of the duloxetine group treatment discontinuation was reported while PGB only had a ratio of 7%. Conclusion: In conclusion despite both drugs having equal efficacy still, the DPNP patients had a better tolerability ratio for pregabalin than duloxetine. Keywords: Type 2 diabetes, Duloxetine, Pregabalin, Peripheral neuropathy pain